Pulsed laser deposition of Ba0.5Sr0.5Co0.8Fe0.2O3−δ thin film cathodes for low temperature solid oxide fuel cells - Li, Yong (2017)
Nanostructured Ba0.5Sr0.5Co0.8Fe0.2O3 − δ (BSCF) thin films were fabricated by pulsed laser deposition (PLD) as a cathode for low-temperature solid oxide fuel cells operated below 500 °C. The nanoscale features in BSCF cathode was obtained by controlling the deposition parameters of PLD including oxygen pressure and substrate temperature. Compared to dense BSCF thin film cathodes, the higher surface area density of surface-roughened BSCF improved the surface reactions of the cathode with ambient oxygen, and therefore effectively improved the cathode performance. Free-standing micro-solid oxide fuel cells with nanostructured BSCF cathode showed a higher peak power density of 55 mW cm− 2 at 450 °C as compared to those using dense BSCF thin film cathode.